Constructive Steganography Using Texture Synthesis. (25th December 2018) - Qian, Zhenxing; Huang, Nannan; Li, Sheng; Zhang, Xinpeng
ABSTRACT: This paper proposes a constructive steganography approach using texture synthesis. With a source texture pattern, we first generate a reference pattern using a point-based texture synthesis. The reference pattern is further extended using a patch-based synthesis algorithm. We crop the extended pattern to generate an intermediate pattern. The reference pattern is then divided into overlapping patches. With a secret key, the reference patches are pseudo-randomly painted onto a blank canvas. To hide secret messages, we identify appropriate patches from the intermediate pattern to represent secret bits, and fulfill the blank regions with these patches using image quilting. The proposed method has a better performance than previous works. As we extend the source pattern to generate more candidate patches, more secret bits can be hidden into the stego image, and the quality of the synthesized image is better. Meanwhile, the proposed method has a capability of resisting a specified attack designed for texture synthesis-based steganography.